A mechanistic IR calibration technique for boiling heat transfer investigations. (July 2016) - Bucci, Matteo; Richenderfer, Andrew; Su, Guan-Yu; McKrell, Thomas; Buongiorno, Jacopo
Highlights: We developed an IR calibration technique to improve the accuracy boiling heat transfer measurements. Suitable for heaters consisting of an IR opaque film coated on an IR semi-transparent substrate. The technique requires the solution of a coupled 3D-conduction/2D-radiation problem. The technique has been validated through experiments supported by a well know analytic solution. Abstract: This paper presents a new calibration technique to improve the accuracy of infrared thermometry in boiling heat transfer investigations. The technique is suitable for heaters consisting of a thin, infrared (IR) opaque conductive film coated on one side of a flat and IR semi-transparent substrate. The conductive film is in contact with the liquid and acts as the boiling surface. The IR camera sees the boiling surface through the substrate. If the substrate is not completely transparent, the radiation emitted by the IR opaque film is partially absorbed and contaminated by the radiation emitted by the substrate itself. Therefore, the correlation between the IR radiation measured by the IR camera and the temperature of the boiling surface (IR opaque film) is not unique, but depends on the temperature distribution in the substrate. To solve this issue, we developed a model that solves the coupled conduction/radiation inverse problem in the heater. The problem is inverse because the boundary condition for the conduction problem (the boiling surface temperature) is not known. The IR camera measures the combined radiation emitted by the boiling surface, emitted by the substrate and also the reflection of the background radiation; from that information one has to reconstruct the boiling surface temperature. The technique is unique in that it takes into account the spectral dependence of optical properties in the optical materials. For this reason, it is particularly suitable for heaters where the optical properties of the conductive film and the substrate materials depend on the wavelength of the IR radiation. Using this technique, we can measure with improved accuracy the time-dependent 3D temperature distribution in the heater, as well as local temperature and local heat flux distributions on the boiling surface. The validation of the technique was carried out using transient conduction experiments. Then, the technique was applied to transient pool boiling experiments to prove its feasibility and show the potential applications.